The Construction of Masculinity in Jihad Selfie Documentary (Proceeding of Dakwah Saizu International Conference, 2023)
This research aims to comprehend the term construction of masculinity. The construction of a 'real man' by showing masculinity can be a reason for someone to be exposed to radical ideologies under the guise of religion. Most individuals who fall into radical groups are not technologically illiterate people. They have strong reasons for joining these groups. The Jihad Selfie film can be a real example for people to think critically about how masculinity could create issues that are conveyed attractively. This study used a qualitative approach with the semiotic analysis technique of Christian Metz to reveal how the Jihad Selfie film constructs masculinity through the relationship between signs that form meaning. Metz's eight-step mapping is used to unravel the typical film structure, i.e. Autonomous Shot, Parallel Syntagma, Bracket Syntagma, Descriptive Syntagma, Alternate Syntagma, Scene, Episodic Sequence, and Ordinary Sequence. The masculinity indicator reveals 5 syntagms that represent masculinity in the form of No Sissy Stuff, Be a Big Wheel, Be a Sturdy Oak, Give ‘em Hell, and New Man as Nurturer